Florida Bromeliad Weevil (no official common name), Metamasius mosieri Barber (Insecta: Coleoptera: Curculionidae: Dryophthorinae) - Barbra Larson; J. Howard Frank; Olan Ray Creel (EDIS)
The Florida bromeliad weevil is an occasional and minor pest on ornamental bromeliads and occurs at very low population densities in its natural habitat. It should not be confused with the Mexican bromeliad weevil, Metamasius callizona, which is currently attacking five species of native bromeliads in 16 counties and will likely destroy populations of six additional species of already-threatened or endangered bromeliads if not brought under control. This document is EENY-209, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2001.